PEMODELAN FAKTOR KEAMANAN LERENG BERBASIS CURAH HUJAN DAN KEMIRINGAN LERENG DI KECAMATAN SUMEDANG SELATAN - Nugraha, Abdurrohman; Upik Nurbaiti; Tri Sri Noor Asih (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
MODELING OF SLOPE SAFETY FACTORS BASED ON RAINFALL AND SLOPE SIDE IN SOUTH SUMEDANG DISTRICT Sumedang Selatan Subdistrict is one of the subdistricts in Sumedang Regency, West Java, which has had many landslide incidents. This is the main reason for the need for landslide disaster mitigation. The first step in landslide disaster mitigation is mathematical modeling as an early warning system. This study aims to model the mathematical equation for the slope safety factor (FK) in Sumedang Selatan Subdistrict based on rainfall data and slope inclination. The mathematical equation used is the Bowles 1996 slope safety factor (FK) equation. The data used are daily rainfall data from 2024 and slope inclination data (DEMNAS) from 2021. The results obtained are graphs of rainfall (P) and slope inclination (θ) against the slope safety factor (FK). The critical point was identified at a daily rainfall of 110 mm and a slope inclination 35°. Rainfall and slope inclination have a negative correlation with the slope safety factor.